Phosphorus in Agriculture: 100 % Zero 2016
DOI: 10.1007/978-94-017-7612-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Energy Neutral Phosphate Fertilizer Production Using High Temperature Reactors

Abstract: Increasing global phosphorus (P) needs and energy demands makes an efficient utilization of finite resources such as phosphate rock (PR) obligatory. The anticipated growth in nuclear energy may require the use of uranium (U) from unconventional resources such as PR as future raw material for nuclear reactor fuel. In parallel, increasing amounts of energy will be needed to process lower grade PR resources in order to satisfy rising phosphate fertilizer requirements for global food production. This work assesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It was found that the quantity of U extracted during fertilizer processing (40.48 t natural U/year) is (after enrichment and fuel manufacture) sufficient to operate three HTR50S units that require the equivalent of 23.71 t natural U/year and provide the electricity needed Fig. Phosphogypsum samples analyzed from the respective plant in the Philippines suggest that REEs worth up to 27.5 million USD (assuming a recovery rate of 50 %) could be extracted annually (Haneklaus et al 2015b). Fuel costs account only for a relatively small portion (<10 %) of the costs associated with HTRs.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the quantity of U extracted during fertilizer processing (40.48 t natural U/year) is (after enrichment and fuel manufacture) sufficient to operate three HTR50S units that require the equivalent of 23.71 t natural U/year and provide the electricity needed Fig. Phosphogypsum samples analyzed from the respective plant in the Philippines suggest that REEs worth up to 27.5 million USD (assuming a recovery rate of 50 %) could be extracted annually (Haneklaus et al 2015b). Fuel costs account only for a relatively small portion (<10 %) of the costs associated with HTRs.…”
Section: Discussionmentioning
confidence: 99%
“…citric, oxalic and galacturonic acid which form stabile complexes with metals, and thus are able to exchange and utilize even strongly bound P (Haneklaus and Schnug 2016a;Nagarajah et al 1970;Oburger et al 2013;Rovira 1965).…”
Section: Turnover Of Inorganic P In Soilsmentioning
confidence: 97%
“…Promising technology has been developed to destroy organic xenobiotics in sewage sludges by incineration combined with solubilization of P and heavy metal extraction which delivers recycled P fertilizer materials that are comparable to manufactured mineral P fertilizers (Adam et al 2009). With view to the contamination of phosphate rock with uranium (U) Haneklaus and Schnug (2016b) developed an innovative concept to employ the extracted U for energy and fertilizer production. Sustainable P fertilization not only requires a complete utilization of the nutrient itself, but also needs to limit collateral damages to soil and food quality.…”
Section: Introductionmentioning
confidence: 99%
“…With the chance of increasing uranium prices, uranium extraction from WPA is once again a very active field of research and new molecules and improved extraction techniques are being developed that may rival traditional open-pit and underground uranium mining as well as in situ leach operations in the near future. During WPA production nuclear process heat from a high temperature reactor (HTR) may best be used for energy intensive calcination prior to the digestion process [62] or providing energy for thermal phosphate rock processing [63][64][65]. At present, approximately 10% of all phosphate rock processed using the wet-acid route is calcined to drive off undesired impurities, notably carbonates and organic matter.…”
Section: Phosphate Rockmentioning
confidence: 99%